Telemedicine in Neuromuscular Diseases During Covid-19 Pandemic: ERN-NMD European Survey - El-Hassar, Lynda; Amara, Ahmed; Sanson, Benoit; Lacatus, Oana; Amir Belhouchet, Ahmed; Kroneman, Madelon; Claeys, Kristl; Plançon, Jean Philippe; Rodolico, Carmelo; Primiano, Guido; Trojsi, Francesca; Filosto, Massimiliano; et al. (Journal of neuromuscular diseases, 2023)
BACKGROUND: Telemedicine (TM) contributes to bridge the gap between healthcare facilities and patients' homes with neuromuscular disease (NMD) because of mobility issues. However, its deployment is limited due to difficulties evaluating subtle neurological signs such as mild weakness or sensory deficits. The COVID-19 pandemic has disrupted healthcare delivery worldwide, necessitating rapid measures implementation by health care providers (HCPs) to protect patients from acquiring SARS-CoV-2 while maintaining the best care and treatment. OBJECTIVES: Given the challenges faced by remote healthcare assistance of NMD patients, we aim to evaluate the use of TM in NMD during the COVID-19 pandemic. METHODS: Based on the Model for Assessment-of-Telemedicine-Applications (MAST), we conducted a survey amongst clinicians of the ERN EURO NMD (European-Reference-Network-for-Rare-Neuromuscular-Diseases). RESULTS: Based on 42 responses over 76 expected ones, our results show that the COVID-19 pandemic significantly increased the number of HCPs using TM (from 60% to 100%). The TM types most used during the COVID-19 period are teleconsultation and consultation by phone, particularly in the context of symptoms worsening in NMD patients with COVID-19 infection. Most European HCPs were satisfied when using TM but as a complementary option to physical consultations. Many responses addressed the issue of technical aspects needing improvement, particularly for elderly patients who need caregivers' assistance for accessing the TM platform. CONCLUSIONS: TM has been essential during COVID-19, but its use still presents some limitations for NMD patients with cognitive deficits or for first-time diagnosis. Thus, TM should be used as complement to, rather than substitute, for face-to-face consultations.
Keywords: Neuromuscular Diseases; neuromuscular diseases; telemedicína; Aged; SARS-CoV-2; lidé; neuromuskulární nemoci; Humans; Pandemics; pandemie; COVID-19; senioři; Telemedicine; Europe; Covid-19